Optimization of heat sterilization on mango fruit (mangifera indica) puree and effects towards cancer treatment - Amid, Azura; Jaswir, Irwandi; Othman, Muhd. Ezza Faiez (IIUM Press, 2011)
Cancer is a disease Which known throughout the world. There are many available commercial and alternative treatments to treat cancer. Mango (Mangifera indica L.) is one the popular tropical fruits found in Malaysia. Mango is a wide variety that can easily be found in this country. It is known for its vibrant flesh colour, juicy texture, sweet flavour, vitamins and minerals. Besides that, mango also contains anticancer and antiprollferation properties. Siamese mango was selected for optimization of puree sterilization. The Design Expert software version 6.0.8 was used to design the experiment to optimize puree sterilization conducted using Central Composite Design with to factor which are variation of temperature (85°C-95°C) and time (1-16 minutes). The optimum condition for the sterilization treatment was at 90°C and 30 seconds holding time.